Expression of macrophage procoagulant activity in murine systemic lupus erythematosus. - Cole, E H (1986)
To explore the induction of monocyte/macrophage procoagulant activity in autoimmune disease, the BXSB murine model of systemic lupus erythematosus was studied. Splenic macrophage procoagulant activity rose coincident with age and the development of glomerulonephritis from 38 +/- 6 mU/10(6) macrophages at 1 mo to a maximum of 29,000 +/- 15,000 mU at 4 mo. Macrophages from 1-mo-old mice could be induced to express a 1,000-fold increase in monocyte/macrophage procoagulant activity when incubated with lymphocytes or lymphocyte supernatants from 5-mo-old mice. Plasma from 5-mo-old but not from 1-mo-old mice was able to induce the production of the lymphokine by cells from 1-mo-old animals. This lymphokine was not interleukin 1,2, or gamma interferon. We conclude that induction of monocyte/macrophage procoagulant activity parallels disease development in the male BXSB mouse, is dependent on the interaction between lymphocytes and plasma factors, and may be important in mediation of injury in lupus nephritis.